The effect of goal orientation on continuous learning activity: Mediating effects of positive & negative feedback seeking behaviors - Kim, Eolim; Han, Tae Young (Korean Journal of Industrial and Organizational Psychology, 2018)
This study focused on motivational characteristics of two goal orientations affecting continuous learning activity. Specifically the study examined effects of performance goal orientation and learning goal orientation on continuous learning activity through mediation effects of two types of feedback seeking behavior - positive and negative feedback seeking behavior. The survey data from 208 employees working in various organizations were analyzed using structure equation analysis. For a comparison, analyses of two goal orientation were conducted separately. Results showed that each goal orientation has positive effects on positive and negative feedback seeking behaviors. While positive feedback seeking behavior was found to affect continuous learning activity positively, negative feedback seeking behavior was not significant. The study revealed that full mediation effect of positive feedback seeking behavior between performance goal orientation and continuous learning activity, and it also found that the effect of learning goal orientation on continuous learning activity was partially mediated by positive feedback seeking behavior. Similar relational patterns were found when the two goal orientations were put in the analysis simultaneously. Suggestions for implications and future research were provided based on the findings.